2008
DOI: 10.3138/cjccj.50.4.491
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Reforms or Maintaining the Status Quo? An Empirical Evaluation of the Judicial Consideration of Aboriginal Status in Sentencing Decisions

Abstract: Government statistics and empirical research have long documented the fact that Aboriginal people account for a much higher proportion of Canada's inmate population than would be expected by looking at their relative proportion in the general population. In spite of this increasing focus on overrepresentation, there has been little documented change in Aboriginal incarceration rates. Section 718.2(e) was added to the Criminal Code to encourage judicial consideration of alternatives to incarceration, with parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 15 publications
5
25
0
Order By: Relevance
“…We located two Indigenous Canadian sentencing disparities studies published over the past 20 years that utilized multivariate statistical techniques (see Weinrath, 2007;Welsh & Ogloff, 2008). These studies found some support for both the differential involvement and positive discrimination hypotheses.…”
Section: Aboriginal Canadian Criminal Defendants and The Imprisonmentmentioning
confidence: 95%
See 4 more Smart Citations
“…We located two Indigenous Canadian sentencing disparities studies published over the past 20 years that utilized multivariate statistical techniques (see Weinrath, 2007;Welsh & Ogloff, 2008). These studies found some support for both the differential involvement and positive discrimination hypotheses.…”
Section: Aboriginal Canadian Criminal Defendants and The Imprisonmentmentioning
confidence: 95%
“…However, the sample used by Welsh and Ogloff (2008) raises two particular problems that limit their research findings. First, the sample of cases was drawn from an electronic legal database that, although noted to be "extensive," did not contain information on all criminal sentencing decisions, with "less serious cases decided on busy court dockets where sentences are imposed with little or no reasons" missing (p. 497).…”
Section: Aboriginal Canadian Criminal Defendants and The Imprisonmentmentioning
confidence: 97%
See 3 more Smart Citations